Tarnishing and Cu Ion release in Selected Copper-Base Alloys: Implications towards Antimicrobial Functionality. (1st July 2015) - Horton, D.J.; Ha, H.; Foster, L.L.; Bindig, H.J.; Scully, J.R.
Abstract: Copper corrosion, tarnishing, release and color stability were investigated in a series of candidate antimicrobial copper alloys Cu, Cu–5Sn, Cu–5Zn–5Al–1Sn, Cu–10Ni–1.5Fe–1Zn, Cu–18Ni–17Zn–1Mn, Cu–20Zn–3Si, and Cu–30Zn ( wt% indicated ). High Cu content, often utilized as an indicator of antimicrobial efficacy brought about by copper release, is shown to be insufficient alone to forecast Cu ion release tendencies during exposure. Alloys were exposed under full immersion in a standardized artificial perspiration solution. Copper release, relative film thickness, the molecular identity of the tarnish, and optical wavelength reflectivity were assessed to determine the fate of copper during oxidation. Copper release did not generally correlate with bulk Cu alloy content, tarnish thickness, or overall corrosion rate due to the unique effects of both major and minor alloying elements. Mechanisms for high or low corrosion rates, tarnishing and Cu release as a function of alloying content are discussed.